Association between psoas muscle mass index and bone mineral density in patients undergoing hemodialysis - Kiyonori Ito; Susumu Ookawara; Hidenori Sanayama; Hideo Kakuda; Chieko Kanai; Katsuo Iguchi; Mitsutoshi Shindo; Keisuke Tanno; Shun Ishibashi; Masafumi Kakei; Kaoru Tabei; Yoshiyuki Morishita (Scientific Reports)
Abstract Patients undergoing dialysis are at risk of osteoporosis and sarcopenia because of mineral and bone disorders or malnutrition. Additionally, maintaining muscle mass is important to prevent osteoporosis. The psoas muscle mass index (PMI) was recently used to evaluate muscle mass. However, few studies have evaluated the association between the PMI and bone mineral density (BMD); therefore, we examined the association between PMI and BMD in the femoral neck (FN) of 80 patients (45 males, age, 71 (60–76) years; dialysis duration, 74 (36–140) months) undergoing hemodialysis. FN-BMD was measured using dual-energy X-ray absorptiometry, and PMI was evaluated using psoas muscle areas on computed tomography. FN-BMD and PMI were significantly higher in males than in females. In a correlation analysis, sex, BMI, serum creatinine levels, HbA1c levels, and PMI were positively correlated with FN-BMD, whereas age, history of bone fracture, difficulty in walking and bone-specific alkaline phosphatase level were negatively correlated. In the multivariate regression analysis using clinical factors significantly correlated to FN-BMD, including PMI, both sex (standardized coefficient: 0.249, p = 0.028) and PMI (standardized coefficient: 0.249, p = 0.038) were extracted. Multivariable linear regression analysis using PMI and traditional osteoporosis factors revealed that PMI was significantly and independently associated with FN-BMD (standardized coefficient: 0.308, p = 0.010). In conclusion, PMI was positively associated with FN-BMD. Attention should be paid to the possibility of decreased BMD with decreased muscle mass.